Unveiling the Potential of Quipper School: A Study on Student Engagement in English Subject - Rasyita Pertiwi (Hasanuddin University, 2024)
This study investigates students' perceptions of Quipper School as an online learning platform and examines its strengths and limitations as an educational medium. Utilizing a descriptive qualitative methodology, informed by L.R. Gay’s framework, data were collected through semi-structured interviews with 6 students from SMAN 8 Makassar. The findings indicate that Quipper School offers several advantages, including free access to instructional videos, a user-friendly interface, comprehensive content delivery, and features that facilitate self-assessment through tasks, quizzes, and summaries. Despite these benefits, challenges were identified, such as network connectivity issues, problems with image display, software glitches, unclear instructional explanations, and language barriers. Overall, Quipper School is perceived as an accessible, user-friendly, and cost-effective tool that enhances the online learning experience.